Effectiveness of Farm Programme Amachi Mati Amachi Mansa perceived by Televiewing Farmers - Deshmukh P.R,; V. T. Wattamwar, (Journal of Agricultural Extension Management, 2025)
Television is recognized as an effective mass medium to spread education, promote social change and rural development. A study was taken up on the perception of the viewers about the effectiveness of the agricultural programme Amachi Mati Amachi Mansa, a television programme in Marathi. The specific objectives were to assess the effectiveness of the programme as perceived by televiewing farmers and to know their expectations about the farm programme. The study revealed that the programme was perceived as useful, effective, and motivating. Some of the suggestions relate to duration of the telecast, programme timings, involvement of progressive farmers in the programme etc.